PENERAPAN MATERIAL PVDF DENGAN POLARISASI PERMUKAAN SEBAGAI SENSOR GAYA - Aditya Nugraha; Masri Bin Ardin (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
PVDF is one of the materials that has piezoelectric properties that are often used  as sensors  or  actuators.  This  piezoelectric property  can be  activated through a stretching process, and then polarized by giving a DC voltage of 4KV. In this study, PVDF material was polarized by the surface polarization method, which were the results tested using d33 meters. The test results show that the value of d33 is 31,32C/N. After being tested using d33 meters, the PVDF material that has been polarized on the surface was tested as a force sensor whose output voltage was measured using an oscilloscope. The result of test carried out by increasing and decreasing load testing and then sensitivity measurements test. The result of increasing and decreasing load test obtained the biggest deviation is 0.35. The results of the calculation of the sensitivity of the PVDF sensor with a surface polarization is 0.0615V / N. Keywords: Surface polarization, Force sensor, PVDF sensor